Science of Semiology: Apply to an Event - Arikli, Melahat (International Review of Management and Marketing, 2016)
Communication materials have initial role in mass communication. Semiology is part of communication and also effective in marketing for traditional worth, it is like compass which give a direction to society in the world. The importance of semiotics and to analyze Eurovision Song Contest, one of the most important musical event of present societies using semiotic method in that study. The objective of the study is to show how important is semiotics, as a part of communicational process. Keywords: Semiotic, culture, message. JEL Classifications: D83, M3